The role of systemic therapy in the management of sinonasal cancer: A critical review. Issue 10 (December 2015) - Bossi, Paolo; Saba, Nabil F.; Vermorken, Jan B.; Strojan, Primoz; Pala, Laura; de Bree, Remco; Rodrigo, Juan Pablo; Lopez, Fernando; Hanna, Ehab Y.; Haigentz, Missak; Takes, Robert P.; Slootweg, Piet J.; et al.
Highlights: A multidisciplinary approach to diagnosis and treatment is needed for SNC. Systemic therapy may play an important role in improving survival in SNC patients, with a possible role in organ/structure preservation. Further studies are needed to identify the optimal sequencing of systemic therapy. Abstract: Purpose: Due to the rarity and the variety of histological types of sinonasal cancers, there is a paucity of data regarding strategy for their optimal treatment. Generally, outcomes of advanced and higher grade tumors remain unsatisfactory, despite the employment of sophisticated surgical approaches, technical advances in radiation techniques and the use of heavy ion particles. In this context, we critically evaluated the role of systemic therapy as part of a multidisciplinary approach to locally advanced disease. Results: Induction chemotherapy has shown encouraging activity and could have a role in the multimodal treatment of patients with advanced sinonasal tumors. For epithelial tumors, the most frequently employed chemotherapy is cisplatin, in combination with either 5-fluorouracil, taxane, ifosfamide, or vincristine. Only limited experiences with concurrent chemoradiation exist with sinonasal cancer. The role of systemic treatment for each histological type (intestinal-type adenocarcinoma, sinonasal undifferentiated carcinoma, sinonasal neuroendocrine carcinoma, olfactory neuroblastoma, sinonasal primary mucosal melanoma, sarcoma) is discussed. Conclusions: The treatment of SNC requires a multimodal approach. Employment of systemic therapy for locally advanced disease could result in better outcomes, and optimize the therapeutic armamentarium. Further studies are needed to precisely define the role of systemic therapy and identify the optimal sequencing for its administration in relation to local therapies.